Composite phase change heat storage material and preparation method thereof

By using nitrogen quantum doped with porous carbon aerogel, acidified paraffin and titanium dioxide-carbon nanotube composites in composite phase change heat storage materials, the problems of low latent heat of phase change, low thermal conductivity and poor cycle stability of existing materials are solved, and the material performance is significantly improved.

CN119505820AActive Publication Date: 2025-02-25SHANDONG GUODIAN INVESTMENT ENERGY MARKETING CO LTD

Patent Information

Application Number
CN202411636733.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing composite phase change heat storage materials have problems such as low latent heat in phase change, low thermal conductivity and poor cycle stability, which limits their application range.

Method used

Nitrogen quantum doped porous carbon aerogel is used as the load carrier, acidified paraffin is combined as the phase change heat storage agent, and titanium dioxide-carbon nanotube composite material is added to jointly improve the latent heat and thermal conductivity of the material while ensuring good cycling stability.

Benefits of technology

It effectively improves the latent heat and thermal conductivity of the composite phase change heat storage material, ensures good cycling stability, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a composite phase change heat storage material and a preparation method thereof, and belongs to the technical field of phase change heat storage materials. The nitrogen quantum dot doped porous carbon aerogel is used as a load carrier, meanwhile, the acidified paraffin is used as a phase change heat storage agent, and the titanium dioxide-carbon nanotube composite material is added for combined action, so that the phase change latent heat and the heat conductivity coefficient of the composite phase change heat storage material can be effectively improved, and good cycle stability is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of phase change heat storage materials, and in particular relates to a composite phase change heat storage material and a preparation method thereof. Background Art

[0002] Phase change materials can achieve reversible phase transitions during isothermal phase transitions to absorb and release a large amount of heat energy, causing the surrounding temperature to rise or fall at a slower rate due to heat changes. Phase change heat storage materials undergo phase transitions during heat exchange and use phase transitions to store energy. They are materials that can absorb or release a large amount of latent heat through phase change processes within a specific temperature range. This property enables phase change materials to effectively store and release heat energy, so they have important application value in many fields and are widely used in building energy conservation, solar thermal utilization, electronic product heat dissipation, transportation and other fields.

[0003] A Chinese patent (publication number CN117025177A) discloses a composite phase-change heat storage material and its preparation method. The invention first uses directional freezing technology to prepare ordered nano copper / carbon nanotube aerogel as a supporting material, and then mixes sodium acetate / potassium acetate and nano copper / carbon nanotube aerogel uniformly dissolved in proportion to form a composite; the composite phase-change heat storage material prepared by this method has a low degree of supercooling, and the porous aerogel adsorbs the phase-change material to effectively inhibit phase separation and prevent leakage during solid-liquid cycle changes. It has a high thermal conductivity coefficient, which can reduce the use of large-area heat exchange tubes and reduce the volume and cost of phase-change heat storage devices. However, the patented technology still does not solve the problems of low phase change latent heat, low thermal conductivity and poor cycle stability in existing composite phase-change heat storage materials, resulting in limited application of composite phase-change heat storage materials.

[0004] Therefore, how to modify the phase change heat storage agent of the composite phase change heat storage material, introduce porous carriers and high thermal conductivity components, effectively improve the phase change latent heat and thermal conductivity of the material, and ensure good cycle stability has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite phase change heat storage material and a preparation method thereof, aiming to solve the problems of the existing composite phase change heat storage materials, such as low phase change latent heat, low thermal conductivity and poor cycle stability.

[0006] The present invention uses nitrogen quantum dot-doped porous carbon aerogel as a load carrier, uses acidified paraffin as a phase change heat storage agent, and adds titanium dioxide-carbon nanotube composite materials to work together, which can effectively improve the phase change latent heat and thermal conductivity of the composite phase change heat storage material and ensure good cycle stability.

[0007] The technical solution of the present invention is as follows:

[0008] A first aspect of the present invention provides a method for preparing a composite phase change heat storage material, comprising the following steps:

[0009] Step S1: by weight, 15 to 20 parts of carbon aerogel and 5 to 10 parts of carbon nanotubes are mixed evenly and placed in a vacuum heating furnace cavity, heat treated in a nitrogen atmosphere, and cooled to obtain a carbon aerogel mixture;

[0010] Step S2: Compounding 20 to 30 parts of the carbon aerogel mixture with 50 to 60 parts of a phase change heat storage agent by vacuum impregnation to obtain a composite phase change heat storage material;

[0011] The carbon aerogel is a nitrogen quantum dot-doped porous carbon aerogel;

[0012] The preparation method of the nitrogen quantum dot-doped porous carbon aerogel comprises: adding 3 to 5 parts of acetic acid to 180 to 200 parts of deionized water by weight, adding 1 to 3 parts of chitosan and stirring for 10 to 20 minutes after mixing evenly, then adding 6 to 8 parts of graphene oxide and 2 to 4 parts of nitrogen quantum dots, stirring for 2 to 4 hours to obtain a dispersion; freezing the dispersion at -4°C for 20 to 24 hours, and then freeze-drying to obtain the nitrogen quantum dot-doped porous carbon aerogel.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] As a preferred technical solution of the present invention, the preparation method of nitrogen quantum dots includes: adding 2 to 4 parts of 2-azidoimidazole to 12 to 16 parts of tetrahydrofuran by weight to fully dissolve, then adding 3 to 4 parts of polyethyleneimine, and reacting at 60 to 65° C. for 20 to 24 hours; after the reaction is completed, adding 1 to 2 parts of deionized water, drying the tetrahydrofuran with a rotary evaporator, and then extracting with ethyl acetate, dialyzing the aqueous phase solution for 8 to 10 hours, filtering with a filter membrane, and freeze-drying the filtrate to obtain nitrogen quantum dots.

[0015] Preferably, the freeze-drying treatment conditions are: freeze-drying temperature is -10°C to -20°C, and freeze-drying time is 40 to 48 hours.

[0016] The porous structure of nitrogen quantum dot-doped porous carbon aerogel can well carry the phase change material and prevent the loss of the phase change material in the molten state. At the same time, the doping of nitrogen quantum dots can change the microstructure of the phase change material and enhance the interaction between molecules, thereby improving the overall stability of the material. In addition, nitrogen quantum dots can also occupy vacancies or interstitial positions in the material, reduce defects, and thus increase cycle stability.

[0017] As a preferred technical solution of the present invention, the carbon nanotubes in step S1 are titanium dioxide-carbon nanotube composite materials; the preparation method of the titanium dioxide-carbon nanotube composite material comprises: weighing 30 to 40 parts of carbon nanotubes, 10 to 15 parts of titanium dioxide, 8 to 10 parts of methyl trioctyl ammonium chloride, 3 to 5 parts of 2-methyl-2,4-pentanediol and 1 to 2 parts of polyethylene glycol, mixing them evenly, and then ball milling and dispersing them for 28 to 30 hours to obtain a mixed slurry, placing the mixed slurry in a nitrogen atmosphere, The titanium dioxide-carbon nanotube composite material is prepared by mixing 80 to 100 parts of the mixed powder in 180 to 200 parts of deionized water and stirring for 1 to 2 hours, then adding 5 to 8 parts of 3-aminopropyltriethoxysilane and stirring for 1 to 2 hours. After the reaction is completed, the titanium dioxide-carbon nanotube composite material is dried at 110 to 120 degrees Celsius for 12 to 14 hours and ground to obtain the titanium dioxide-carbon nanotube composite material.

[0018] Carbon nanotubes have very high thermal conductivity, which can enhance the thermal conductivity of composite materials, ensure uniform heat distribution during the heat storage process, and reduce thermal hysteresis during the heat storage process. At the same time, the introduction of titanium dioxide through modification treatment can form more thermal conduction paths and improve the efficiency of heat energy transfer. The combination of carbon nanotubes and titanium dioxide can effectively improve the thermal conductivity of composite phase change heat storage materials.

[0019] Preferably, the heat treatment in step S1 is performed at a temperature of 800 to 900° C. and for a time of 1 to 2 hours.

[0020] As a preferred technical solution of the present invention, the phase change heat storage agent in step S2 is paraffin; the paraffin is acidified paraffin; the preparation method of the acidified paraffin comprises: adding 100 to 120 parts of paraffin by weight to a reactor with a stirrer, heating to 170 to 175°C; then adding 20 to 25 parts of maleic anhydride and 10 to 15 parts of boric acid, stirring for 1 to 2 hours under nitrogen protection, then adding 8 to 10 parts of dibenzoyl peroxide, controlling the temperature to 175 to 180°C, reacting for 1 to 3 hours, and obtaining the acidified paraffin after purification.

[0021] Acidified paraffin can introduce polar groups such as carboxyl groups into the paraffin molecules through acidification treatment. Polar groups can increase the interaction between molecules, improve crystallinity and order, and thus increase the phase change latent heat of the composite phase change heat storage material.

[0022] Preferably, the vacuum degree of the vacuum impregnation treatment in step S2 is 0.07-0.09 MPa, the temperature is 50-100° C., and the time is 2-4 hours.

[0023] The second aspect of the present invention provides a composite phase change heat storage material prepared by the method described in the first aspect.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention uses acidified paraffin as a phase change heat storage agent, modifies the paraffin by using maleic anhydride and boric acid, introduces polar groups such as carboxyl, and uses the polar groups to increase the interaction between paraffin molecules, improve crystallinity and order, and effectively increase the phase change latent heat of the composite phase change heat storage material.

[0026] (2) The carbon nanotubes in the titanium dioxide-carbon nanotube composite material of the present invention can ensure uniform heat distribution during the heat storage process and reduce thermal hysteresis during the heat storage process. The titanium dioxide can form more heat conduction paths and improve the efficiency of heat energy transfer. The two work together to effectively improve the thermal conductivity of the composite phase change heat storage material. At the same time, the boron element in the acidified paraffin is combined with the nitrogen quantum dots in the nitrogen quantum dot-doped porous carbon aerogel, further improving the thermal conductivity of the material.

[0027] (3) The nitrogen quantum dot-doped porous carbon aerogel of the present invention changes the microstructure of the phase change material by introducing nitrogen quantum dots, thereby enhancing the intermolecular interaction force. At the same time, the nitrogen quantum dots effectively occupy the interstitial positions in the material and reduce defects, thereby improving the cycle stability. In addition, the amino groups contained in the titanium dioxide-carbon nanotube composite material will combine with the groups in the acidified paraffin to form a network interconnected structure, further improving the cycle stability of the material.

[0028] (4) The carbon aerogel with micron-sized pores of the present invention is beneficial to the phase change process of the phase change heat storage agent. The carbon nanotubes have high thermal conductivity, which ensures uniform heat distribution during the heat storage process and enhances the strength and light absorption capacity of the composite material. The composite of carbon aerogel and carbon nanotubes can improve the thermal response speed of the phase change material and increase its thermal stability. DETAILED DESCRIPTION

[0029] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0030] The sources of some components in the embodiments and comparative examples are as follows:

[0031] Carbon aerogel, item number 002, was purchased from Tianjin Deruifengkai New Material Technology Co., Ltd.;

[0032] Carbon nanotubes, catalog number Pas1004, were purchased from Hongna New Materials Technology Co., Ltd.;

[0033] Paraffin wax, product number M5310, was purchased from Anhui Zesheng Technology Co., Ltd.;

[0034] 2-Azimidazole, CAS No. 56751-68-9, purchased from Tianjin Yankai Technology Co., Ltd.;

[0035] Tetrahydrofuran, CAS No. 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0036] Polyethyleneimine, product number E107079, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0037] Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0038] Acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0039] Chitosan, product number KJT01, was purchased from Xi'an Shizeyuan Biotechnology Co., Ltd.;

[0040] Graphene oxide, product number DN-20DY, was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.;

[0041] Titanium dioxide, product number R-996, purchased from Dongguan Wohai Trading Co., Ltd.;

[0042] Methyltrioctyl ammonium chloride, CAS No. 5137-55-3, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] 2-Methyl-2,4-pentanediol, CAS No. 107-41-5, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] Polyethylene glycol, catalog number PA73288, was purchased from Shanghai Chuangsai Technology Co., Ltd.;

[0045] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0046] Maleic anhydride, CAS No. 108-31-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0047] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0048] Dibenzoyl peroxide, CAS No. 94-36-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0049] Preparation of nitrogen quantum dots: In parts by weight, 4 parts of 2-azidoimidazole are added to 16 parts of tetrahydrofuran and fully dissolved, and then 4 parts of polyethyleneimine are added and reacted at 60°C for 24 hours; after the reaction is completed, 2 parts of deionized water are added, and the tetrahydrofuran is dried by a rotary evaporator, and then extracted with ethyl acetate. The aqueous phase solution is dialyzed for 8 to 10 hours, filtered with a filter membrane, and the filtrate is freeze-dried (the freeze-drying temperature is -10°C and the freeze-drying time is 48 hours) to obtain nitrogen quantum dots.

[0050] Preparation of titanium dioxide-carbon nanotube composite material: 40 parts of carbon nanotubes, 15 parts of titanium dioxide, 10 parts of methyl trioctyl ammonium chloride, 5 parts of 2-methyl-2,4-pentanediol and 2 parts of polyethylene glycol are weighed in parts by weight, mixed evenly and dispersed by ball milling for 30 hours to obtain a mixed slurry, the mixed slurry is placed in a nitrogen atmosphere, treated at 800°C for 10 hours, cooled to room temperature, dried, crushed and ground to obtain a mixed powder; 100 parts of the mixed powder are added to 200 parts of deionized water and stirred for 2 hours, and then 8 parts of 3-aminopropyltriethoxysilane are added, stirred for reaction for 2 hours, and after the reaction is completed, it is dried at 120°C for 12 hours, and ground to obtain a titanium dioxide-carbon nanotube composite material.

[0051] Preparation of acidified paraffin: By weight, 120 parts of paraffin are added to a reactor with a stirrer and heated to 175°C; then 25 parts of maleic anhydride and 15 parts of boric acid are added, stirred for 2 hours under nitrogen protection, and then 10 parts of dibenzoyl peroxide are added, the temperature is controlled at 180°C and the reaction is carried out for 3 hours, and the acidified paraffin is obtained after purification.

[0052] Example 1

[0053] This embodiment provides a method for preparing a composite phase change heat storage material, comprising the following steps:

[0054] The preparation method of nitrogen quantum dot-doped porous carbon aerogel comprises: adding 5 parts of acetic acid to 200 parts of deionized water by weight, adding 3 parts of chitosan and stirring for 20 minutes after mixing evenly, then adding 8 parts of graphene oxide and 4 parts of nitrogen quantum dots, stirring for 4 hours to obtain a dispersion; freezing the dispersion at -4°C for 24 hours, and then freeze-drying to obtain nitrogen quantum dot-doped porous carbon aerogel.

[0055] Step S1: 20 parts by weight of nitrogen quantum dot-doped porous carbon aerogel and 10 parts of titanium dioxide-carbon nanotube composite material are mixed evenly and placed in a vacuum heating furnace cavity, and heat treated in a nitrogen atmosphere (temperature of 900° C., time of 1 h), and then cooled to obtain a carbon aerogel mixture;

[0056] Step S2: In parts by weight, 30 parts of the carbon aerogel mixture and 60 parts of acidified paraffin are compounded with each other through vacuum impregnation treatment (vacuum degree of 0.09 MPa, temperature of 100° C., time of 2 h) to obtain a composite phase change heat storage material.

[0057] Example 2

[0058] This embodiment provides a method for preparing a composite phase change heat storage material, comprising the following steps:

[0059] The preparation method of nitrogen quantum dot-doped porous carbon aerogel comprises: adding 3 parts of acetic acid to 180 parts of deionized water by weight, adding 1 part of chitosan and stirring for 10 minutes after mixing evenly, then adding 6 parts of graphene oxide and 2 parts of nitrogen quantum dots, stirring for 2 hours to obtain a dispersion; freezing the dispersion at -4°C for 20 hours, and then freeze-drying to obtain nitrogen quantum dot-doped porous carbon aerogel.

[0060] Step S1: by weight, 15 parts of nitrogen quantum dot-doped porous carbon aerogel and 5 parts of titanium dioxide-carbon nanotube composite material are mixed evenly and placed in a vacuum heating furnace cavity, and heat treated under a nitrogen atmosphere (temperature of 800° C., time of 2 h), and a carbon aerogel mixture is obtained after cooling;

[0061] Step S2: In parts by weight, 20 parts of the carbon aerogel mixture are compounded with 50 parts of acidified paraffin by vacuum impregnation treatment (vacuum degree of 0.07 MPa, temperature of 50° C., time of 4 h) to obtain a composite phase change heat storage material.

[0062] Example 3

[0063] This embodiment provides a method for preparing a composite phase change heat storage material, comprising the following steps:

[0064] The preparation method of nitrogen quantum dot-doped porous carbon aerogel comprises: adding 4 parts of acetic acid to 190 parts of deionized water by weight, adding 2 parts of chitosan and stirring for 15 minutes after mixing evenly, then adding 7 parts of graphene oxide and 3 parts of nitrogen quantum dots, stirring for 3 hours to obtain a dispersion; freezing the dispersion at -4°C for 22 hours, and then freeze-drying to obtain nitrogen quantum dot-doped porous carbon aerogel.

[0065] Step S1: 18 parts by weight of nitrogen quantum dot-doped porous carbon aerogel and 6 parts of titanium dioxide-carbon nanotube composite material are mixed evenly and placed in a vacuum heating furnace cavity, and heat treated under a nitrogen atmosphere (temperature of 850° C. for 2 h), and then cooled to obtain a carbon aerogel mixture;

[0066] Step S2: In parts by weight, 25 parts of the carbon aerogel mixture are compounded with 55 parts of acidified paraffin by vacuum impregnation treatment (vacuum degree of 0.08 MPa, temperature of 80° C., time of 3 h) to obtain a composite phase change heat storage material.

[0067] Comparative Example 1

[0068] This comparative example provides a method for preparing a composite phase change heat storage material. The difference from Example 1 is that commercially available carbon aerogel is used instead of nitrogen quantum dot-doped porous carbon aerogel, commercially available carbon nanotubes are used instead of titanium dioxide-carbon nanotube composite materials, and commercially available paraffin is used instead of acidified paraffin.

[0069] Comparative Example 2

[0070] This comparative example provides a method for preparing a composite phase-change heat storage material, which differs from Example 1 in that commercially available carbon nanotubes are used instead of the titanium dioxide-carbon nanotube composite material, and commercially available paraffin is used instead of acidified paraffin.

[0071] Comparative Example 3

[0072] This comparative example provides a method for preparing a composite phase change heat storage material, which differs from Example 1 in that commercially available carbon aerogel is used instead of nitrogen quantum dot-doped porous carbon aerogel, and commercially available paraffin is used instead of acidified paraffin.

[0073] Comparative Example 4

[0074] This comparative example provides a method for preparing a composite phase change heat storage material. The difference from Example 1 is that commercially available carbon aerogel is used instead of nitrogen quantum dot-doped porous carbon aerogel, and commercially available carbon nanotubes are used instead of titanium dioxide-carbon nanotube composite materials.

[0075] Comparative Example 5

[0076] This comparative example provides a method for preparing a composite phase change heat storage material, which differs from Example 1 in that commercially available carbon aerogel is used instead of nitrogen quantum dot-doped porous carbon aerogel.

[0077] Comparative Example 6

[0078] This comparative example provides a method for preparing a composite phase change heat storage material. The difference from Example 1 is that commercially available carbon nanotubes are used instead of the titanium dioxide-carbon nanotube composite material.

[0079] Comparative Example 7

[0080] This comparative example provides a method for preparing a composite phase-change heat storage material, which differs from Example 1 in that commercially available paraffin is used instead of acidified paraffin.

[0081] The following tests were performed on the performance of the composite phase change heat storage materials prepared in the above embodiments and comparative examples:

[0082] Phase change latent heat test: The test was carried out using a synchronous thermal analyzer (TGA / DSC 3+, Mettler-Toledo GmbH, Switzerland). 10 mg of the composite phase change heat storage material prepared in the embodiment and the comparative example was placed in a crucible, and linearly heated / cooled at a rate of 2°C / min in a nitrogen atmosphere with a flow rate of 5 mL / min. The temperature range was 30-120°C, and the DSC curve was obtained and the phase change latent heat was calculated using the built-in formula of the instrument.

[0083] Thermal conductivity test: The test was performed using a thermal constant analyzer (TPS2500, Hot Disk Ltd., Sweden). 0.5 g of the composite phase change heat storage material prepared in the embodiment and the comparative example was pressed into a disc with a diameter of 12.7 mm and a thickness of 5 mm at a pressure of 8 MPa using a tablet press. The probe was clamped in the middle with the phase change material disc at room temperature. The probe model was 5501, the test time was set to 20 s, the power was set to 20 mW, and the thermal conductivity was obtained after measurement.

[0084] Cyclic stability test: The composite phase change heat storage materials prepared in the embodiments and comparative examples were used as samples before cyclic testing; the composite phase change heat storage materials prepared in the embodiments and comparative examples were placed in a constant temperature drying oven at 90°C and heated for 2 hours, taken out and naturally cooled to room temperature, and the above operation process was repeated 100 times to obtain samples after cyclic testing; a synchronous thermal analyzer (TGA / DSC 3+, Mettler-Toledo GmbH, Switzerland) was used to test the samples before and after the cyclic testing, respectively, and the phase change enthalpy change rate was obtained by comparing the curves of the two tests.

[0085] The test data is shown in Table 1:

[0086] Table 1 Performance test results

[0087] Latent heat of phase change (kJ / kg) Thermal conductivity (W / (m·K)) Phase change enthalpy change rate (%) Example 1 223.88 28.75 2.38 Example 2 221.75 28.69 2.51 Example 3 222.82 28.71 2.44 Comparative Example 1 206.03 21.28 5.51 Comparative Example 2 208.45 21.32 4.12 Comparative Example 3 209.41 24.55 5.34 Comparative Example 4 219.72 21.28 5.28 Comparative Example 5 219.85 24.58 4.13 Comparative Example 6 219.93 24.61 4.11 Comparative Example 7 210.08 24.59 4.12

[0088] From the above content, it can be seen that the present invention uses nitrogen quantum dots doped porous carbon aerogel as a load carrier, uses acidified paraffin as a phase change heat storage agent, and adds titanium dioxide-carbon nanotube composite materials to work together to obtain a composite phase change heat storage material (Example 1 to Example 3), whose phase change latent heat is 221.75~223.88kJ / kg, thermal conductivity is 28.69~28.75W / (m·K), and phase change enthalpy change rate is 2.38~2.51%.

[0089] Compared with Example 1, commercially available carbon aerogel is used to replace nitrogen quantum dot-doped porous carbon aerogel, commercially available carbon nanotubes are used to replace titanium dioxide-carbon nanotube composite materials, and commercially available paraffin is used to replace acidified paraffin, then the phase change latent heat is reduced, the thermal conductivity is reduced, and the phase change enthalpy change rate is increased (Comparative Example 1); Compared with Example 1, commercially available carbon nanotubes are used to replace titanium dioxide-carbon nanotube composite materials, and commercially available paraffin is used to replace acidified paraffin, then the phase change latent heat is reduced, the thermal conductivity is reduced, and the phase change enthalpy change rate is increased (Comparative Example 2); Compared with Example 1, commercially available carbon aerogel is used to replace nitrogen quantum dot-doped porous carbon aerogel, and commercially available paraffin is used to replace acidified paraffin, then the phase change latent heat is reduced, the thermal conductivity is reduced, and the phase change enthalpy change rate is increased (Comparative Example 2). Comparative Example 3); Compared with Example 1, commercially available carbon aerogel is used to replace nitrogen quantum dot-doped porous carbon aerogel, and commercially available carbon nanotubes are used to replace titanium dioxide-carbon nanotube composite materials, then the thermal conductivity is reduced and the phase change enthalpy change rate is increased (Comparative Example 4); Compared with Example 1, commercially available carbon aerogel is used to replace nitrogen quantum dot-doped porous carbon aerogel, then the thermal conductivity is reduced and the phase change enthalpy change rate is increased (Comparative Example 5); Compared with Example 1, commercially available carbon nanotubes are used to replace titanium dioxide-carbon nanotube composite materials, then the thermal conductivity is reduced and the phase change enthalpy change rate is increased (Comparative Example 6); Compared with Example 1, commercially available paraffin is used to replace acidified paraffin, then the phase change latent heat is reduced, the thermal conductivity is reduced, and the phase change enthalpy change rate is increased (Comparative Example 7).

[0090] In summary, the present invention uses nitrogen quantum dots doped porous carbon aerogel as a load carrier, uses acidified paraffin as a phase change heat storage agent, and adds titanium dioxide-carbon nanotube composite materials to effectively improve the phase change latent heat and thermal conductivity of the composite phase change heat storage material and ensure good cycle stability.

[0091] The applicant declares that the present invention uses the above embodiments to illustrate the detailed process flow of the present invention, but the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention falls within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite phase change heat storage material, characterized in that: The following steps are involved: Step S1: by weight, 15 to 20 parts of carbon aerogel and 5 to 10 parts of carbon nanotubes are mixed evenly and placed in a vacuum heating furnace cavity, heat treated in a nitrogen atmosphere, and cooled to obtain a carbon aerogel mixture; Step S2: Compounding 20 to 30 parts of the carbon aerogel mixture with 50 to 60 parts of a phase change heat storage agent by vacuum impregnation to obtain a composite phase change heat storage material; The carbon aerogel is a nitrogen quantum dot-doped porous carbon aerogel; The preparation method of the nitrogen quantum dot-doped porous carbon aerogel comprises: adding 3 to 5 parts of acetic acid to 180 to 200 parts of deionized water by weight, adding 1 to 3 parts of chitosan and stirring for 10 to 20 minutes after mixing evenly, then adding 6 to 8 parts of graphene oxide and 2 to 4 parts of nitrogen quantum dots, stirring for 2 to 4 hours to obtain a dispersion; freezing the dispersion at -4°C for 20 to 24 hours, and then freeze-drying to obtain the nitrogen quantum dot-doped porous carbon aerogel.

2. The method for preparing the composite phase change heat storage material according to claim 1, characterized in that: The preparation method of nitrogen quantum dots comprises: adding 2 to 4 parts of 2-azidoimidazole to 12 to 16 parts of tetrahydrofuran by weight to fully dissolve, then adding 3 to 4 parts of polyethyleneimine, and reacting at 60 to 65° C. for 20 to 24 hours; after the reaction is completed, adding 1 to 2 parts of deionized water, drying the tetrahydrofuran with a rotary evaporator, extracting with ethyl acetate, dialyzing the aqueous solution for 8 to 10 hours, filtering with a filter membrane, and freeze-drying the filtrate to obtain nitrogen quantum dots.

3. The method for preparing the composite phase change heat storage material according to claim 2, characterized in that: The freeze-drying treatment conditions are: freeze-drying temperature is -10°C to -20°C, and freeze-drying time is 40 to 48 hours.

4. The method for preparing the composite phase change heat storage material according to claim 1, characterized in that: The carbon nanotubes described in step S1 are titanium dioxide-carbon nanotube composite materials.

5. The method for preparing the composite phase change heat storage material according to claim 4, characterized in that: The preparation method of the titanium dioxide-carbon nanotube composite material comprises: weighing 30 to 40 parts of carbon nanotubes, 10 to 15 parts of titanium dioxide, 8 to 10 parts of methyl trioctyl ammonium chloride, 3 to 5 parts of 2-methyl-2,4-pentanediol and 1 to 2 parts of polyethylene glycol by weight, mixing them evenly, and then ball milling and dispersing them for 28 to 30 hours to obtain a mixed slurry; placing the mixed slurry in a nitrogen atmosphere, treating it at 780 to 800° C. for 10 to 12 hours, cooling it to room temperature, drying it, crushing it, and grinding it to obtain a mixed powder; adding 80 to 100 parts of the mixed powder into 180 to 200 parts of deionized water, stirring it for 1 to 2 hours, then adding 5 to 8 parts of 3-aminopropyl triethoxysilane, stirring it for 1 to 2 hours, drying it at 110 to 120° C. for 12 to 14 hours after the reaction is completed, and grinding it to obtain the titanium dioxide-carbon nanotube composite material.

6. The method for preparing the composite phase change heat storage material according to claim 1, characterized in that: The heat treatment in step S1 is performed at a temperature of 800 to 900° C. and for a time of 1 to 2 hours.

7. The method for preparing the composite phase change heat storage material according to claim 1, characterized in that: The phase change heat storage agent in step S2 is paraffin.

8. The method for preparing the composite phase change heat storage material according to claim 7, characterized in that: The paraffin wax is acidified paraffin wax; the preparation method of the acidified paraffin wax comprises: adding 100 to 120 parts of paraffin wax by weight into a reaction kettle with a stirrer, heating to 170 to 175° C.; then adding 20 to 25 parts of maleic anhydride and 10 to 15 parts of boric acid, stirring for 1 to 2 hours under nitrogen protection, then adding 8 to 10 parts of dibenzoyl peroxide, controlling the temperature to 175 to 180° C., reacting for 1 to 3 hours, and obtaining the acidified paraffin wax after purification.

9. The method for preparing the composite phase change heat storage material according to claim 1, characterized in that: The vacuum degree of the vacuum impregnation treatment in step S2 is 0.07-0.09 MPa, the temperature is 50-100° C., and the time is 2-4 hours.

10. A composite phase change heat storage material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon nanotube aerogel-based composite shaped phase change material and preparation and application thereof

    CN114106779A

  • Composite phase change heat storage material and preparation method thereof

    CN117025177A

  • Guar gum and graphite carbon nitride carbon aerogel-based composite phase change material as well as preparation method and application thereof

    CN117645864A

  • Use of polymer dispersions as heat exchange fluids

    US20130341556A1

  • Dynamic polymer having hybridized cross-linked network and use thereof

    WO2018045866A1

Cited By

  • MXene synergistic composite phase change heat storage material and preparation method thereof

    CN120484785A